EVALUASI INDIKATOR TOLERANSI CEKAMAN KEKERINGAN PADA FASE PERKECAMBAHAN PADI (ORYZA SATIVA L.) - SONG, NIO; TONDAIS, SRI MARIYATI; BUTARBUTAR, REGINA (Jurnal Biologi Udayana; Vol 14 No 2 (2010): Jurnal Biologi, 2010)
A study was conducted to evaluate morphological characters that were able to be used as indicators of water-deficit tolerance in rice at the germination phase in the Laboratory of Conservation Biology and Biodiversity, Department of Biology, FMIPA, Sam Ratulangi University. The method that was used in this study was germination in the osmoticum solution. Rice cultivars Mira 1 and IR 64 were used and the osmoticum solution was polyethylene glycol (PEG) 8000. Among the morphological characters (i.e. length of seminal root, shoot length, root-to-shoot length ratio, coleoptile length, germination percentage and seed vigour index) that were evaluated, root-to-shoot length ratio was able to be used as the indicator of water-deficit tolerance in rice at the germination phase.
Keywords: morphological charateristics; polyethylene glycol 8000; root-to-shoot length ratio